Propuesta para el ordenamiento de los sistemas de gestión del agua en los países de América Latina y el Caribe - Dourojeanni , Axel (1992)
It specifically analyzes how it is carried out and how the management of water resources can be improved for its integral management. It is emphasized that what is really important is to give a comprehensive treatment to the water system, its collection and evacuation basins, regardless of whether the management system itself is integrated or not. To facilitate the analysis a systemic approach is used. The conceptual framework provides a classification of management levels into four categories: scientific-environmental, economic-productive, technical-normative and political-social; these levels are associated with different management areas. In order to conduct environmental management processes, in particular for management of water resources for multiple use, two delimitation criteria must be taken into account: the political-administrative and the geographical-ecological. If management systems are brought together in relation to these two limits, it is possible to arrive at a more effective form of environmental management.